The Evolution of Transbronchial Lung Biopsy Guidance - Alatas, Mohammad Fahmi; Bies, Asri Liqditta; Prasenohadi, Prasenohadi; Soehardiman, Dicky; Aniwdyaningsih, Wahju; Elhidsi, Mia; Desianti, Ginanjar Arum; Reisa, Tina; Rasmin, Menaldi (Respiratory Science, 2025)
Histological confirmation of lung lesions is necessary prior to determining further management. Imaging preparation is needed to find the biopsy site such as a computed tomography scan. Imaging helps to trace the position of lung lesions that are peripheral and not visualized by bronchoscope. However, along with the discovery of small lesions and peripheral location, two-dimensional imaging alone remains suboptimal. Therefore, to reach lung lesions peripherally would need to a guide through the bronchial. Subsequently, the method of guiding transbronchial biopsy evolved. Namely, real-time fluoroscopy, radial-probe endobronchial ultrasound, virtual bronchoscopy navigation and electromagnetic bronchoscopy navigation are guiding modalities with each of their advantages and disadvantages. Several biopsy modalities are used in combination to increase the accuracy of diagnosis. Careful analysis in planning and an understanding of the limitations and advantages of diagnostic modalities must be considered in deciding which method to choose.